2016
DOI: 10.14740/gr672w
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rectal Diclofenac Suppository for Prevention and Its Impact on Severity of Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis in High-Risk Patients

Abstract: BackgroundThe aim was to study the role of rectal diclofenac in prevention of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis and its impact on severity of post-ERCP pancreatitis.MethodsWe conducted a single-center, prospective, open-labeled, randomized trial for evaluating the use of rectal diclofenac in prevention of post-ERCP pancreatitis in high-risk patients. We assessed 526 patients coming for ERCP for different indications. Four hundred patients were eligible for the study. Those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…This slightly changed the OR and the SUCRA, indicating low heterogeneity ( I 2 = 2.47%, P = 0.48). The exclusion of two open-label studies[ 18 , 23 ] also did not change the final results.…”
Section: Resultsmentioning
confidence: 99%
“…This slightly changed the OR and the SUCRA, indicating low heterogeneity ( I 2 = 2.47%, P = 0.48). The exclusion of two open-label studies[ 18 , 23 ] also did not change the final results.…”
Section: Resultsmentioning
confidence: 99%
“…The stratification of the PEP risk and the use of diclofenac only in the high-risk group are controversial and evidence shows contradictory results (7,13).…”
Section: Discussionmentioning
confidence: 99%
“…This inflammatory cascade activation is the cause of local and systemic effects. The proposed surgeries to prevent PEP seek to break this inflammatory cascade (3,6,7).…”
Section: Original Articlementioning
confidence: 99%
“…In an in vitro experiment, diclofenac was shown to reduce the activity of PLA2 by 93%, if used at high concentrations (14) . Previous studies performed in India and England showed that diclofenac administered via the rectal route decreased the incidence and severity of PEP (17,18) . Conversely, another study performed in Indiana, USA, failed to demonstrate similar results with respect to the use of oral diclofenac in high-risk patients (19) .…”
Section: Variablesmentioning
confidence: 91%